PENGARUH DEWAN KOMISARIS, LEVERAGE, DAN STRUKTUR KEPEMILIKAN TERHADAP PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT (ERM) - Cecasmi, Jetmi Ade; samin, Samin (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
The purpose of this study was to examine the influence of Board of Commissioner, Leverage, and Ownership Structure on the Enterprise Risk Management disclosure of banking firm listed in Indonesian Stock Exchange for the period from 2013 to 2015. Sampling technique using purposive sampling (purposive sampling method). The sampel used in this study is a banking company that meets the criteriaas set out in this study to obtain 21 banking. The data obtained derived from the annualreport and financial report of the banks publishe. The analysis technique used in this research is multiple linear regression to test the classical assumption first. The result showed that the Board of Commissioner have a significant influence on the Enterprise Risk Management Disclosure. Leverageand Ownership Structure is not significantly effects on Enterprise Risk Management Disclosure.